Forensic Expertise Digitalization and The Use of Modern Technologies (International Journal of Scientific Trends, 2026)
The article presents a scientific analysis of reforms aimed at modernizing forensic expert activity in the Republic of Uzbekistan, their legal foundations, the processes of digitalization of forensic expert activity, as well as the main problems encountered in practice. The author scientifically substantiates that the harmonious development of the forensic expert system in line with global trends and the digitalization of activities are important factors in increasing the effectiveness of justice.